REFOCUSING, RELOKASIANGGARAN DAN PERTANGGUNGJAWABAN APBD DALAM MASA PANDEMI COVID-19 DI PROVINSI PAPUA BARAT TAHUN 2020 - Sugiyono Sugiyono; Adolf Z.D. Siahay; Simson Werimon (Universitas Cenderawasih, 2021)
Sugiyono, 2021. Refocusing, Budget Reallocation and Accountability of the Regional Budget during the 2020 West Papua Covid-19 Pandemic, supervised by Mr. Adolf Z. D. Siahay, as Advisor I and Mr. Samson Werimon, as Advisor II. The purpose of this study was to analyze the impact of refocusing, budget relocation and budget accountability during the 2020 West Papua Covid-19 pandemic.This type of research is qualified as descriptive qualitative research with data collection techniques obtained through observation, interviews, documentation and internet access. Primary data in this study were interviews with the Head of BPK Representative for West Papua Province and Head of BPKAD for West Papua Province and secondary data was obtained from Financial Audit Reports by BPK in 2019 and 2020.The results of the study prove that the Covid-19 Pandemic has a very wide impact both in terms of government, politics, and the economy as well as society, including the drastic decline in the performance of APBD management. The 2020 Covid-19 Fund Allocation was Rp. 779,114,469,608.75, with an absorption value of 36.56%. The Weakness of the 2019 APBD Management was 0.028% while the 2020 APBD management performance decreased by 0.390%. The percentage of the Covid-19 budget management performance value in 2020 was found to be lower by 11.81% or the management was less than optimal.